CLINICAL AND SONOGRAPHIC FINDINGS IN HORSES AFFECTED WITH CHRONIC FLEXOR TENDINOPATHIES AND ASSOCIATED SOFT TISSUE INJURIES OF VARIOUS JOINTS - A. Ullah; S. G. Bokhari; S. Aslam; S. Masood; A. Noor; U. Israr (Journal of Animal and Plant Sciences, 2021)
Flexor tendinopathies and injuries to ligaments along with arthropathies are common in athletic horses. In this study, forty-eight client-owned healthy and injured horses, suffering from chronic tendinitis, fetlock arthritis and pain/swelling in other joints, were selected and divided into three equal groups (n=16) i.e. Group A (Race), Group B (Polo) and Group C (Draft horses); each group comprised of two equal sub-groups i.e. sound (n=8) and unsound (n=8). Chronic superficial and deep digital flexor (SDFT and DDFT) tendinopathies, as well as ligament injuries from various joints (elbow, carpus, fetlock, stifle and hock) were assessed. Thorough clinical and sonographic assessments were performed. Percentage prevalence of injuries depicted fetlock collateral ligament injuries to be of highest in occurrence (50%) in the Race Horse Group A, while flexor tendinopathies (50%) were greatest in the Polo horse Group B. Contrastingly, the Draft Horse Group C manifested greater prevalence of carpus, fetlock, stifle and hock injuries (25%). All unsound horses manifested with statistically significant clinical parameters of swelling, pain, lameness and reduced range of motion. Sonographically, unsound Race and Polo horses presented with lesion hyperechogenicity (P≤0.014), fiber pattern disruption (P≤0.002 and P≤0.007, respectively), and heterogeneity (P≤0.002). Severity of injury was highly significant (P≤0.003) in Groups A (Race) and C (Draft). Race and Polo horses manifested greater unsoundness (P≤0.002), with a poorer prognosis (P≤0.001), as compared to Draft horses (unsoundness: P≤0.012; prognosis: P≤0.006). Conclusively, injuries were more pronounced in Race horses, followed by Polo and Draft horses, respectively.
Keywords: ultrasonography; tendons; ligaments; joints; horses; soundness